Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada CV. Nelayan Percut Makmur Medan - Zalukhu, Bintari Mei Arthana; Saragih, Nahar Maganda (Universitas Gajah Putih, 2023)
Customer satisfaction is a person's feelings of pleasure or disappointment arising from comparing the performance that has been perceived against their expectations. This study aims to determine or analyze the effect of price and product quality on customer satisfaction at CV. Percut Prosperous Fishermen in Medan. This type of research is quantitative. The types of data used are primary and secondary data obtained from questionnaires. This research was conducted on customers of CV. Fishermen of Percut Makmur Medan with a sample of 92 respondents who were taken by purposive sampling method with a sampling technique using the slovin formula. The analytical method used is multiple linear regression analysis. The results of the analysis show that the price and product quality together or simultaneously have a positive and significant influence on the customer satisfaction variable at CV. Percut Prosperous Fishermen in Medan. Partially the price has a positive and significant effect on the customer satisfaction variable at CV. Percut Prosperous Fishermen in Medan. Partially, product quality has a positive and significant effect on customer satisfaction variables in CV. Percut Prosperous Fishermen in Medan. Keywords: Price, Product Quality And Customer Satisfaction.